A retrospective study of WeChat app-based health management for patients with gestational diabetes mellitus - Biyun Huang; Huimin Zhai (Taylor & Francis Group, 2025)
Background This study aimed to explore and evaluate the effectiveness of WeChat app-based health management in patients with gestational diabetes mellitus (GDM).Methods This study retrospectively analysed a cohort of 100 patients with GDM. Since the application we used went live in April 2023, we enrolled patients from April 2022 to June 2022 into the control group (n = 50) and patients from April 2023 to June 2023 into the observation group (n = 50) for contemporaneous comparisons. The control group received routine health management procedures, whereas the observation group received app-based health management. Fasting plasma glucose, 2-hour postprandial blood glucose, and haemoglobin A1c levels were compared between the two groups before and four and eight weeks after app management; the incidence of adverse pregnancy outcomes and weight gain before and after pregnancy was also compared between the two groups.Results Fasting plasma glucose and 2-hour postprandial blood glucose levels were lower in the observation group than in the control group four and eight weeks after intervention (p < 0.05). In addition, the incidence of adverse pregnancy outcomes and weight gain was lower in the observation group than in the control group (p < 0.05).Conclusions Implementing WeChat app-based health management can effectively improve blood glucose levels, reduce adverse pregnancy events in patients with GDM, and decrease weight gain during pregnancy.